PERAN PENDIDIKAN AGAMA ISLAM DALAM PEMBINAAN MORAL GENERASI Z DI SEKOLAH MULTIKULTURAL - Hengki Satrisno; Al Fauzan Amin; Dhioba Sinata; Fakhri Muhammad Ramadhan; Geon Protomo (STKIP Subang, 2025)
This study examines the role of Islamic Religious Education (PAI) in strengthening the moral character of Generation Z in multicultural school environments. The research aims to identify PAI-based strategies used to foster tolerance, honesty, discipline, and cooperation among students with diverse cultural and religious backgrounds. Using a descriptive qualitative method, data were collected through in-depth interviews with Gen Z students, PAI teachers, non-PAI teachers, and student council members, as well as through observation and documentation. The findings indicate that PAI plays educative, preventive, and integrative roles in moral formation. Moral violations such as bullying, minor conflicts, and indiscipline decreased significantly after PAI-based interventions. The study concludes that PAI contributes effectively to developing moral knowledge, moral feeling, and moral action, while creating a harmonious multicultural school climate.